Group Identities Make Fragile Tipping Points - Sönke Ehret; Sara M. Constantino; Elke U. Weber; Charles Efferson; Sonja Vogt (Center for Economic Studies and ifo Institute (CESifo), 2022)
Social tipping can accelerate beneficial changes in behaviour in diverse domains from equality and social justice to climate change. Hypothetically, however, group identities might undermine tipping in ways policy makers do not anticipate. To examine this, we implemented an experiment around the 2020 U.S. elections. Participants faced consistent incentives to coordinate their choices. Once participants had established a coordination norm, an intervention created pressure to tip to a new norm. Our control treatment used neutral labels for choices. Our identity treatment used partisan political images. This simple payoff-irrelevant relabelling generated extreme differences. Control groups developed norms slowly before intervention but transitioned to new norms rapidly after intervention. Identity groups developed norms rapidly before intervention but persisted in a state of costly disagreement after intervention. Tipping was powerful but fragile. It supported striking cultural changes when choices and identity were unlinked, but even a trivial link destroyed tipping entirely.
Keywords: Z10; Z13; Z18; 330; social tipping; cultural evolution; behaviour change; coordination